2021
DOI: 10.1007/s00603-021-02624-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Anisotropic Mechanical Properties of Oil Shales Under Real-Time High-Temperature Conditions

Abstract: The anisotropic mechanical and acoustic emission characteristics of oil shale from room temperature to 600 °C were studied using a real-time high-temperature uniaxial rock testing machine independently developed by the Taiyuan University of Technology and an acoustic emission test system. The results indicate that the elastic modulus and compressive strength of the oil shale perpendicular to bedding direction first decrease and then increase with increasing temperature from room temperature to 600 °C and reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Previous investigations into the dynamic evolution of the porosity and permeability of shale and oil shale under increasing temperature have observed similar trends to those identified in the present study [13,29,49,50,[52][53][54][55][56][57][58]. The dynamic evolution of the porosity and permeability of oil shale with increasing temperature was generally consistent with that of shale, and the temperature threshold for the sharp increase in the porosity and permeability in both oil shale and shale was approximately 350 • C (Figure 12).…”
Section: Changes In Shale Porosity and Permeability During Heatingsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous investigations into the dynamic evolution of the porosity and permeability of shale and oil shale under increasing temperature have observed similar trends to those identified in the present study [13,29,49,50,[52][53][54][55][56][57][58]. The dynamic evolution of the porosity and permeability of oil shale with increasing temperature was generally consistent with that of shale, and the temperature threshold for the sharp increase in the porosity and permeability in both oil shale and shale was approximately 350 • C (Figure 12).…”
Section: Changes In Shale Porosity and Permeability During Heatingsupporting
confidence: 87%
“…The porosity increased by 10-times, and the permeability increased by 2-4 orders of magnitude (Table 2). Previous studies have shown that, when oil shale is heated above 400 °C, the porosity and permeability increase substantially [49][50][51][52][53][54][55][56][57][58]. Our compilation of published data revealed that the porosity was generally <5% and the horizontal permeability was generally <0.1 md before heating, increasing to around 15-30% and 0.1-100 md after heating to 400-450 °C, respectively.…”
Section: Changes In Shale Porosity and Permeability During Heatingmentioning
confidence: 56%
“…Horizontal permeability increases faster with porosity than with vertical permeability. The oil and gas transformed from the shale in situ conversion can be transported better horizontally and cannot be well transported vertically, which is favorable for later exploitation. , …”
Section: Resultsmentioning
confidence: 99%
“…The oil and gas transformed from the shale in situ conversion can be transported better horizontally and cannot be well transported vertically, which is favorable for later exploitation. 64,65 3.4. Comparative Analysis of Model-Calculated and Experimental Values.…”
Section: Evaluation Model Of Permeabilitymentioning
confidence: 99%
“…Alneasan [12] investigated the effect of temperature on the fracture characteristics of granite under three loading modes and found that the fracture behavior was temperature-dependent and could be changed from brittle to ductile. Wang [13] investigated the anisotropic mechanical behavior of oil shale from room temperature to 600°C using a real-time high-temperature test system.…”
Section: Introductionmentioning
confidence: 99%